THE PENGARUH NANOLIPOSOME EKSTRAK KUNYIT DAN LADA HITAM TERHADAP JUMLAH SEL MAKROFAG PADA PENYEMBUHAN ULKUS TRAUMATIK MUKOSA LABIAL TIKUS WISTAR: PENGARUH NANOLIPOSOME EKSTRAK KUNYIT DAN LADA HITAM TERHADAP JUMLAH SEL MAKROFAG PADA PENYEMBUHAN ULKUS TRAUMATIK MUKOSA LABIAL TIKUS WISTAR - Fuadiyah, Diena; Nafa, Achmad Zulhafidz (E-Prodenta Journal of Dentistry, 2026)
Background : Ulkus is a common condition frequently encountered in daily life, particularly in the oral cavity, and often causes painful disruptions to daily activities. Traumatic ulcers appear as single, oval lesions that can heal within less than a week after the causative factor is removed. However, some cases of traumatic ulcers do not heal spontaneously and can lead to serious complications such as infection and further tissue damage. Objective : The purpose of this study is to investigate the effect of nanoliposome extracts of turmeric (Curcuma longa L.) and black pepper (Piper nigrum) on the number of macrophages during the healing process of traumatic ulcers in the labial mucosa of Wistar rats (Rattus norvegicus). Methods : The method used in this study is a true experimental design conducted in vivo, using a randomized post test only control group design. The research object is 45 male Wistar rats (Rattus norvegicus), divided into 15 groups: three control groups (K3, K5, and K7) and 12 treatment groups (P3A, P3B, P3C, P3D, P5A, P5B, P5C, P5D, P7A, P7B, P7C, and P7D). Result : The results show a significant increase in the number of macrophages at day 5 compared to the control groups (p < 0.05) between days 3 and 7.Conclusion : Nanoliposome extracts of turmeric and black pepper play a role in increasing the number of macrophages during the healing process of labial mucosa ulcers in Wistar rats on day 5 post-heat induction.